Two new terrestrial species of Hydraena Kugelann from the island of Bioko, Gulf of Guinea (Coleoptera: Hydraenidae) - Hernando, Carles; Ribera, Ignacio (Zootaxa, 2017)
The knowledge of the Hydraenidae of sub-Saharan Africa, and in particular of the genus Hydraena Kugelann, 1794, is most incomplete. As an example, in southern Africa only three species were described before the revision of Perkins (2014), which raised the number to 31. Only 15 species are currently known from Central Africa, between the Sahel and South Africa, all belonging to subgenus Hydraenopsis Janssens, 1972 (Trizzino et al. 2013), but many more remain to be described and discovered. The islands of the Gulf of Guinea are no exception to this lack of knowledge (Jones 1994), and only one species of the family was previously known, H. (Hydraenopsis) pagaluensis Hernando & Ribera, 2001 from Annobón (Hernando & Ribera 2001; Trizzino et al. 2013). In this paper we describe the first known species of Hydraenidae from Bioko, the largest and closest to the continent of these islands. The species were collected by our friend and colleague Vasily Grebennikov during a survey of the forest litter fauna of Annobón and Bioko. Despite considerable efforts no Hydraenidae were found in Annobón, and only these two species, in a single locality, in Bioko.